2019
DOI: 10.3390/ijerph16183404
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Distribution of Precipitation in Huang-Huai-Hai River Basin between 1961 to 2016, China

Abstract: The Huang-huai-hai River Basin is one of the most economically developed areas, but is also heavily impacted by drought and flood disasters. Research on the precipitation feature of the Huang-huai-hai River Basin is of great importance to the further discussion of the cause of flood disaster. Based on the selected meteorological stations of the study area from 1961–2016, the inverse distance weighting method was used to get daily precipitation grid data. Interannual variation of precipitation intensity and cov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…Unlike the general “dry-get-drier, wet-get-wetter” paradigm under a warming climate, precipitation was found to decline during past decades and increase in future decades throughout the DQRB (Figs. 5 and 6 ), similar to the results obtained in previous studies (Song et al 2015 ; Yuan et al 2019 ; Li et al 2016a ; Li et al 2018b ). This result is considered to be related to the Western Pacific subtropical high, which determines the intensity of the East Asian monsoon (Wang et al 2019 ); i.e., moisture transport and convergence with weak large-scale circulation are insufficient to deliver abundant moisture, while the strengthened and unstable East Asian summer monsoon north of 30° N enhances the availability of water vapor.…”
Section: Discussionsupporting
confidence: 91%
“…Unlike the general “dry-get-drier, wet-get-wetter” paradigm under a warming climate, precipitation was found to decline during past decades and increase in future decades throughout the DQRB (Figs. 5 and 6 ), similar to the results obtained in previous studies (Song et al 2015 ; Yuan et al 2019 ; Li et al 2016a ; Li et al 2018b ). This result is considered to be related to the Western Pacific subtropical high, which determines the intensity of the East Asian monsoon (Wang et al 2019 ); i.e., moisture transport and convergence with weak large-scale circulation are insufficient to deliver abundant moisture, while the strengthened and unstable East Asian summer monsoon north of 30° N enhances the availability of water vapor.…”
Section: Discussionsupporting
confidence: 91%
“…In previous studies, there were many methods that focused on hazard factors used to study flood and drought disasters, such as the drought index and extreme precipitation (Guo et al, 2018;Yang et al, 2018a;Yuan et al, 2019;Zuo et al, 2019). The hazard factors indicate the intensity of the water anomalies, which represent the direct cause of the disaster.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies recommend the Weibull distribution as the optimal PDF of the observed precipitation in the DQRB in comparison to the common parametric distributions (Shi et al, 2014;Li and Shi, 2019). It should be that the precipitation distristructure of the DQRB has changed in the past few decades (Yuan et al, 2019). Thus, DKDE may be more preferred to represent the PDF of the observed precipitation.…”
Section: Discussionmentioning
confidence: 99%